2016
DOI: 10.1002/2016wr018651
|View full text |Cite
|
Sign up to set email alerts
|

Excess warming of a Central European lake driven by solar brightening

Abstract: Recent trends in summer surface temperatures of many lakes exceed the corresponding air temperature trends. This disagrees with expectations from lake surface heat budgets, which predict that lake surface temperatures should increase by 75–90% of the increase in air temperatures. Here we investigate the causes for this excess warming for Lower Lake Zurich, a representative deep and stratified Central European lake, by a combined data analysis and modeling approach. Lake temperatures are simulated using a one‐d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
97
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(110 citation statements)
references
References 61 publications
(73 reference statements)
7
97
2
Order By: Relevance
“…For the deep lakes (especially for Lake Geneva), the calibrated values of the α parameter tend to be higher than the ones found by previous studies, which ranged from 0.001 to 0.03 for large basins (Schmid and Köster, 2016;Fink et al, 2014b;Finger et al, 2007). There are several reasons that can explain this deviation.…”
Section: Calibration Resultscontrasting
confidence: 57%
“…For the deep lakes (especially for Lake Geneva), the calibrated values of the α parameter tend to be higher than the ones found by previous studies, which ranged from 0.001 to 0.03 for large basins (Schmid and Köster, 2016;Fink et al, 2014b;Finger et al, 2007). There are several reasons that can explain this deviation.…”
Section: Calibration Resultscontrasting
confidence: 57%
“…It should also be noted that air2water may be limited when dealing with changes in water transparency (as has been the case for Lake Tahoe during the last 50 yr, Jassby et al ; Tahoe Environmental Research Center 2016), which likely modify the parameter governing the stratification dynamics (i.e., δ). In addition, the effect of other factors such as changes in solar brightening or wind forcing during the validation period (compared to the calibration period) cannot be directly captured by the simple structure of the model (except, indirectly, through their potential effect on AT ), despite the fact that they have been shown to be important in some lakes (Schmid and Köster ; Woolway et al ). These considerations undoubtedly challenge the application of the model.…”
Section: Resultsmentioning
confidence: 99%
“…Solar brightening [39,48] and decreases in cloud cover [49] lead to increased solar radiation reaching the lake surface. Schmid and Köster [39] found that 60% of LSWT in a central European lake was attributable to increasing air temperature, while the remaining 40% was attributable to increased solar radiation due to air quality improvements. In the future, LSWT warming rates may be more consistent with air temperature rates depending on future stabilization in air quality improvements [4,39].…”
Section: Near-surface Warmingmentioning
confidence: 99%
“…Schmid and Köster [39] found that 60% of LSWT in a central European lake was attributable to increasing air temperature, while the remaining 40% was attributable to increased solar radiation due to air quality improvements. In the future, LSWT warming rates may be more consistent with air temperature rates depending on future stabilization in air quality improvements [4,39]. Similarly, milder winters, shortening ice cover and less snow cover on ice occurring in NENA and around the northern latitudes [50,51] will all contribute to lowered lake albedo, earlier stratification and longer duration of energy absorption, resulting in intensified summer warming [11,12,52].…”
Section: Near-surface Warmingmentioning
confidence: 99%